Breeding behavior and chick development of king bird-of-paradise (Cicinnurus regius) at Bird Park Jagat Satwa Nusantara - Basyuri, Ade; Kombo, Muhammad Piter; Akbar, Wahyu Nalendra; Gusti, Caesar Rizal Kurniawan; Kristanto, Ady; Khan, Muhammad Fardhan; Mukharliza, Arisa (Journal of Wildlife and Conservation Medicine, 2025)
Background The king bird-of-paradise (Cicinnurus regius) is endemic to Papua and Papua New Guinea's lowland rainforests. Its population declines due to habitat loss from deforestation, illegal hunting, and trafficking. As a protected species, urgent conservation efforts are needed. Ex-situ breeding programs can support its long-term survival.Objective The present study analyzed breeding behavior patterns, including maternal care, feed palatability during breeding and non-breeding phases, environmental factors that influence breeding success, and chick development.Methods The research employed purposive sampling and instantaneous sampling techniques. Observations were conducted on maternal behavior, feed preference, and environmental conditions (temperature and humidity) within the enclosure, and chick development to obtain comprehensive data on breeding activities.Results Maternal care behavior: dominated by the flying (36.44%), perching (33.78%), and the parent feeding the chick (7.98%). Feed palatability: highest for crickets (92.4%) during the breeding phase and weaver ant eggs (100%) during the non-breeding phase. Environmental factors: cage temperature ranged from 27°C–29°C with humidity levels between 89%–91%. Observation of maternal behavior, feed palatability, and environmental factors resulted in healthy chick development, as evidenced by the chick’s ability to leave the nest and begin reaching for its food at 17 days of age.Conclusion The findings highlight the critical role of maternal care, high-quality feed, and stable environmental conditions in supporting the successful breeding and healthy chick development of the king bird-of-paradise (C. regius) in captivity. This study contributes valuable knowledge to strengthen ex-situ conservation strategies for this protected and ecologically significant species.